Hasil Tes Aerobik Dilihat dari Urutan Item Tes berdasarkan Sumber Energi - Akbar, Muhammad Syagill; Imanudin, Iman; Umaran, Unun (Jurnal Simki Pedagogia, 2025)
Testing and measurement is one of the disciplines that must be carried out and understood by coaches if they want to create an athlete. One of the references for sorting test items is physiological principles. The research uses a quasi-experimental design with repetitated measures. The population of this study is sports science students of the University of Education Indonesia who contract test and measurement courses using saturated sampling techniques. Based on the results of the hypothesis test from the results of data processing and analysis using the SPSS application, there is a difference between the results of the aerobic test conducted at the beginning and the aerobic test conducted at the end). Based on the results of the research conducted, ES-I (strength, muscle endurance, and nerve coordination) should come first, and then followed by ES-II (cardiovascular endurance), because the accumulation of lactic acid from aerobic tests can interfere with the performance of the muscles involved in other tests. This aims to maximize the performance of both energy systems and avoid interference between energy sources.